Wild Boars as an Indicator of Environmental Spread of ESβL-Producing Escherichia coli - Mercato, Alessandra; Cortimiglia, Claudia; Abualsha’ar, Aseel; Piazza, Aurora; Marchesini, Federica; Milani, Giovanni; Bonardi, Silvia; Cocconcelli, Pier Sandro; Migliavacca, Roberta (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) represents an increasing issue worldwide, spreading not only in humans and farmed animals but also in wildlife. One of the most relevant problems is represented by Extended-Spectrum Beta-Lactamases (ESβLs) producing Escherichia coli because they are the cause of important infections in human. Wild boars (Sus scrofa) as a source of ESβLs attracted attention due to their increasing density and their habits that lead them to be at the human-livestock-wildlife interface. The aim of this study was to increase the knowledge about the ESβLs E. coli strains carried by wild boars living in a particularly high-density area of Northern Italy. The analysis of 60 animals allowed to isolate 16 ESβL-producing E. coli strains (prevalence 23.3%), which were characterised from a phenotypical and molecular point of view. The overall analysis revealed that the 16 isolates were all not only ESβL producers but also multidrug resistant and carried different types of plasmid replicons. The genome analysis performed on a subset of isolates confirmed the heterogeneity observed with pulsed-field gel electrophoresis (PFGE) and highlighted the presence of two pandemic sequence types, ST131 and ST10, with different collections of virulence factors. The genomic context of ESβL genes further evidenced that all of them were surrounded by transposons and insertion sequences, suggesting the possibility to exchange AMR genes. Overall, this study shows the worrying dissemination of ESβL-producing E. coli in wild boars in Northern Italy, suggesting the role of these animals as a spreader of AMR and their inclusion in surveillance programmes, to shed light on the “One Health” complex interactions.